Oxford international primary English student book 4 - Danihel, Emma; Hearn, Izabella (Pakistan : Oxford University Press, 2022)
Oxford International Primary English Book 4 offers a rich, globally-oriented curriculum designed to strengthen Grade 4 students' English reading, writing, speaking, and listening skills. Aligned with the Oxford International Curriculum, PYP framework, and Pakistan$1 (Bs Single National Curriculum, the text incorporates thematic units featuring both fiction and nonfiction extracts from varied international sources. Each unit includes vocabulary highlights, reading comprehension exercises, speaking and listening scaffolds, and step-by-step writing workshops with models and writing frames. Teachers benefit from structured frameworks, clear learning objectives, and measurable assessment criteria to confidently guide instruction and monitor student progress.s
Keywords: English - Text Book